Negative regulation of receptor tyrosine kinases by ubiquitination: Key roles of the Cbl family of E3 ubiquitin ligases - Tang, Rong; Langdon, Wallace Y.; Zhang, Jian (Frontiers in Endocrinology, 2022)
Receptor tyrosine kinases (RTKs) serve as transmembrane receptors that participate in a broad spectrum of cellular processes including cellular growth, motility, differentiation, proliferation, and metabolism. Hence, elucidating the regulatory mechanisms of RTKs involved in an assortment of diseases such as cancers attracts increasing interest from researchers. Members of the Cbl family ubiquitin ligases (c-Cbl, Cbl-b and Cbl-c in mammals) have emerged as negative regulators of activated RTKs. Upon activation of RTKs by growth factors, Cbl binds to RTKs via its tyrosine kinase binding (TKB) domain and targets them for ubiquitination, thus facilitating their degradation and negative regulation of RTK signaling. RTKs such as epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor (PDGF), fibroblast growth factor receptor (FGFR) and hepatocyte growth factor receptor (HGFR) undergo ubiquitination upon interaction with Cbl family members. In this review, we summarize the current knowledge related to the negative regulation of RTKs by Cbl family proteins.